Andrea Nagy, Valerio Severino & Orsolya Varsányi (a cura di), Az elysioni aszfodéloszok közt, Kerényi Károly és Angelo Brelich levelezése 1935–1959 - Mohácsy, Eszter (Verbum – Analecta Neolatina, 2021)
Andrea Nagy, Valerio Severino & Orsolya Varsányi (a cura di), Az elysioni aszfodéloszok közt, Kerényi Károly és Angelo Brelich levelezése 1935–1959, Budapest: L'Harmattan, 2020, 286 p.